PENGARUH IKLAN TELEVISI DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE DI BALI - Ni Kadek Ratna Kumalasari; Ni Putu Nita Anggraini; Pande Ketut Ribek (VALUES, 2022)
Growing using marketplace where as online shopping is driven by the technological advances that it becomes a trend to the society. Through increase of sales, required of many companies to participate using the digitization currently. Television advertising and online customer reviews is one of the factors that can effect purchase decisions. A unique and good television commercials will be easier in the mind of consumers the brand. The existence feature of online customer review can decrease received risk of possibility to consumers online shopping, therefore companies and merchants that can get of the trust while consumer of making purchase decisions. This research aims to analyze the effect of television advertising and online customer reviews on purchase decisions. The research population is all the Shopee users in Bali with was 100 respondents of sample based on purposive sampling technique. The data was collected by distributing questionnaire by multiple linear regression analysis. The results of analysis regression show that television advertising and online customer review the partial has positive and significant effect on purchase decisions. Based on this result, we can suggested that Shopee must to increase of the frequency broadcasting television advertising and continue to improve advertising innovate and online review features to create more purchase decisions. Television advertising on the research have a dominant impact on purchase decisions.